Exploring the effects of physical exercise on inferiority feeling in children and adolescents with disabilities: a test of chain mediated effects of self-depletion and self-efficacy - Yang, Tongnian; Xiao, Hui; Fan, Xiaoyan; Zeng, Wenping (Frontiers in Psychology, 2023)
Objective The purpose of this study was to investigate the effects of physical exercise on inferiority feeling of children and adolescents with disabilities and its mechanism of action, as well as the mediating role of self depletion and self-efficacy. Methods The following scales were administered to 546 children and adolescents with disabilities (mean age 15.6 years): The Feelings of Inadequacy Scale, (FIS), the Self-Regulation Fatigue Scale (S-RFS), the General Self-Efficacy Scale (GSES), and the Physical Exercise Rating Scale. Results (1) Physical exercise can directly and negatively predict inferiority feeling, self-depletion, and can directly and positively predict self-efficacy; self-depletion can directly and negatively predict self-efficacy. Similarly, self-depletion positively predicts inferiority feeling; physical exercise and self-efficacy can also directly and negatively predict inferiority feeling. (2) The indirect effect of the path with self-depletion as the mediating variable was – 0.05, the indirect effect of the path with self-efficacy as the mediating variable was – 0.09, and the indirect effect of the path with self-depletion and self-efficacy as the mediating variables was – 0.04. (3) The sum of all indirect effects was – 0.18, and the three indirect effects accounted for 15.6%, 28.1%, and 12.5% of the total effect, with mediating effect was 56.2%. Conclusion Physical exercise can indirectly predict inferiority feeling in children and adolescents with disabilities through the independent mediation of self-depletion and self-efficacy, as well as through the chain mediation of both. This study supports that moderate physical exercise has a positive effect on the mental health of children and adolescents with disabilities, and that reducing self-depletion and improving self-efficacy are important ways to prevent inferiority feeling among children and adolescents with disabilities. It reveals the relationship between physical exercise and inferiority feeling and its mechanism of action, and further improves the research on the effect of physical exercise on inferiority feeling of children and adolescents with disabilities.